Edge illumination X-ray phase contrast imaging for impact damage detection in CFRP. (June 2022) - Shoukroun, D.; Massimi, L.; Endrizzi, M.; Bate, D.; Fromme, P.; Olivo, A.
Abstract: Carbon fibre reinforced polymer (CFRP) structures are widely used in the aerospace industry for their low weight and strong mechanical properties. However, they are prone to impact damage due to their brittle nature. Edge Illumination X-ray Phase Contrast imaging (EI XPCi), a novel, phase-based X-ray imaging technique, was compared against two established non-destructive evaluation methods for impact damage detection in CFRP plates. Planar EI XPCi was shown to allow the detection of a larger extent and more details of damage than both conventional X-ray imaging using contrast agents and ultrasonic immersion C-scans. However, both X-ray methods were unable to detect a delamination present in the plate, which was only observed from the ultrasonic C-scan. Planar EI XPCI has potential for rapid in-process scanning, where only 2D projection imaging is possible. Graphical Abstract: ga1